Low Energy Ultrapulse CO2 Fractional Laser Combined with Autologous Platelet-Rich Plasma in Periorbital Rejuvenation Treatment - Yanwen Qi; Cheng Sun; Yang Zhou; Lizhou Luo; Chengyuan Wang (Journal of Investigative Surgery)
Objective This paper focuses on the efficacy of low energy ultrapulsed CO2 fractional laser (LEUCO2FL) combined with autologous platelet-rich plasma (PRP) in periorbital rejuvenation treatment.Methods Eighty patients with periorbital wrinkles and eyelid laxity were randomly assigned to a laser group (n = 40) receiving LEUCO2FL or a combination group (n = 40) receiving additional autologous PRP. Both groups received treatment once per month for a total of three sessions. Cosmetic outcomes were assessed at three months post-treatment using the Global Esthetic Improvement Scale (GAIS). VISIA (wrinkles, texture), SOFT (skin elasticity, moisture), upper eyelid depression, and infraorbital hollowing were evaluated before and at 1, 3, and 6 months post-treatment. Adverse reactions and patient satisfaction were recorded.Results The combination group exhibited higher overall effective rate of GAIS, greater improvements in wrinkles, texture, skin elasticity, and moisture at all time points, and lower upper eyelid depression and infraorbital hollowing scores than the laser group. While both treatments were well tolerated, patient satisfaction was higher in the combined group than the laser group.Conclusion LEUCO2FL combined with autologous PRP demonstrates favorable cosmetic effects in periorbital rejuvenation, significantly improving periorbital wrinkles and texture, enhancing skin elasticity and hydration, and reducing periorbital hollowness.